Teletrabajo, género y gentrificación o elitización en los espacios rurales: nuevos usos y nuevos protagonistas. Los casos de Cataluña y Ardéche (Francia) - Cánoves Valiente, Gemma; Blanco Romero, Asunción (Geographicalia, 2016)
Rural spaces present a clear change in social composition and uses. The present article shows these new dynamics by gender composition, teleworking and gentrification. The article compares the cases of Catalonia and Ardechein France, which are in different dynamics and temporal periods. The material research has combined statistics and in-deep interviews. The results show telework as a non-consolidated option in Catalonia; also exposes that women adopt this formula in punctual moments, and rural spaces have incorporated new population with clear strategies of social and economic diversification.